2001
DOI: 10.1111/j.1752-0606.2001.tb01137.x
|View full text |Cite
|
Sign up to set email alerts
|

Reconstituting Racial Histories and Identities: The Narratives of Interracial Couples

Abstract: This study explores the process by which interracial spouses construct narratives about their racial histories, identities, and experiences in their relationship together. Ten black-white couples were interviewed individually and conjointly. The results reflected interracial spouses' experience of their life together, their perception of others' perceptions of them, and their unique processes of negotiating racial, gender, and class differences. Black spouses, compared with white spouses, demonstrated a greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
1
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 15 publications
1
78
1
5
Order By: Relevance
“…However, as families grow more multicultural, interfaith, and international, intergroup issues are going to appear as more prominent concerns (Killian, 2001). Moreover, intergroup scholars have begun to recognize that communication within relational units, such as the family, offers unique possibilities COMMUNICATION AND GROUP SALIENCE for their own work-particularly in terms of exploiting some of the inherent identity connections within the family for the benefit of changing intergroup attitudes (Anderson et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…However, as families grow more multicultural, interfaith, and international, intergroup issues are going to appear as more prominent concerns (Killian, 2001). Moreover, intergroup scholars have begun to recognize that communication within relational units, such as the family, offers unique possibilities COMMUNICATION AND GROUP SALIENCE for their own work-particularly in terms of exploiting some of the inherent identity connections within the family for the benefit of changing intergroup attitudes (Anderson et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…Killian (2001) also found that in some instances, friends of interracial couples would even go so far as to tell a person not to go through with the wedding on the wedding day. Social support potentially influences both the amount of conflict and the conflict strategies of members of interracial couples, with such individuals experiencing less social support than members of same-race couples.…”
Section: Conflict and The Microsystemmentioning
confidence: 93%
“…Then, the researcher can look at some preliminary themes and bring the family together to investigate these themes further, or ask the family to process questions as a unit to see if new meaning arises through interaction. Killian (2001) interviewed interracial spouses both individually and together with the purpose of allowing individual spouses to share feelings that might not have been expressed in the presence of the other partner. One disadvantage to this approach is the time needed to conduct three or more interviews.…”
Section: Individual and Couple/family Interviewsmentioning
confidence: 99%
“…The person involved in the testing was given the choice of whether to be interviewed individually or with the family together, and all chose with their family. Killian (2001Killian ( , 2002 used a mixed approach with couples who were interviewed separately and together. Killian examined how couples construct narratives about their racial histories and identities.…”
Section: Rationale For Decision Of Whom To Interviewmentioning
confidence: 99%